Perempuan-perempuan yang Memahkotai Kelamin Dengan Sastra - Indradi, Agustinus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2006)
In many traditional communities, sex is considered a unsuitable subject to discuss or at least to talk about openly. This notion is in fact still intact in Indonesia, including among urban communities. Therefore, when sexuality is chosen to be the theme of a novel, moreover written by a woman, it becomes a subject of controversy and raises a lot of open debate and polemic. Apart from many objections, some Indonesian woman writters keep the subject alive in modern Indonesian literature. The author highlights the potrait of